Classical myths in Italian Renaissance painting - Freedman, Luba (Cambridge University Press, 2011)
"The book is about a new development in Italian Renaissance art; its aim is to show how artists and humanists came together to effect this revolution, it is important because this is a long-ignored but crucial aspect of the Italian Renaissance, showing us why the masterpieces we take for granted are the way they are, and thre is no competitor in the field. The book sheds light on some of the world's greatest masterpirces of art, including Botticelli's Venus, Leonardo's Leda, Raphael's Galatea, and Titian's Bacchus and Ariadne"--